1971
DOI: 10.1042/cs0410013
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ventilatory Response to Carbon Dioxide during Recovery from Severe Asthma

Abstract: i. Ventilatory response to CO 2 was measured regularly by a rebreathing technique in nineteen patients with severe asthma from the day of presentation to the time of clinical recovery.2. Ventilatory response to CO 2 increased during recovery in sixteen patients and the increased ventilatory response correlated well with increase of FEVr-Among these sixteen patients only one showed elevation of arterial CO 2 tension at the time of presentation.3. Ventilatory response to CO 2 failed to increase during recovery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 14 publications
4
30
0
Order By: Relevance
“…For example, long-term hypoxemia-induced DVH has been observed in residents living at high altitude (34,35) and in patients with congenital cyanotic heart disease (8). However, available data showed that some asthmatic patients with DVH exhibited hypoxemia (14,15,26,31), whereas others did not (21,32). Although DVH is generally observed in asthmatic individuals, the results concerning the ventilatory response to hypercapnia were controversial.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…For example, long-term hypoxemia-induced DVH has been observed in residents living at high altitude (34,35) and in patients with congenital cyanotic heart disease (8). However, available data showed that some asthmatic patients with DVH exhibited hypoxemia (14,15,26,31), whereas others did not (21,32). Although DVH is generally observed in asthmatic individuals, the results concerning the ventilatory response to hypercapnia were controversial.…”
mentioning
confidence: 87%
“…We found that Ova-exposure caused DVH in guinea pigs without significant changes in Pa O 2 and Pa CO 2 during eupneic breathing, demonstrating that DVH is not the result of preexisting hypoxemia. In fact, hypoxemia is not uniformly observed in asthmatic individuals (3,14,15,21,26,31,32) and not necessarily related to the degree of asthmatic severity (21). In addition, Ova treatment in guinea pigs failed to change body weight, baseline cardiorespiratory activities, baseline total pulmonary resistance, and dynamic lung compli- ance (41).…”
Section: Presence Of Dvh In Ova Guinea Pigs Provides a Useful Animal mentioning
confidence: 99%
See 3 more Smart Citations